Metadata and Semantics Research 7th International Conference, MSTR 2013, Thessaloniki, Greece, November 19-22, 2013. Proceedings - Garoufallou, Emmanouel.; Garoufallou, Emmanouel.; Greenberg, Jane.; Greenberg, Jane. (Communications in Computer and Information Science,, 2013)
This book constitutes the refereed proceedings of the 7th Metadata and Semantics Research Conference, MTSR 2013, held in Thessaloniki, Greece, in November 2013. The 29 revised papers presented were carefully reviewed and selected from 89 submissions. The papers are organized in several sessions and tracks. The sessions cover the following topics: platforms for research datasets, system architecture and data management; metadata and ontology validation, evaluation, mapping and interoperability; content management. The tracks cover the following topics: big data and digital libraries in health, science and technology; European and national projects and project networking; metadata and semantics for open repositories, research information systems and data infrastructures; metadata and semantics for cultural collections and applications; metadata and semantics for agriculture, food and environment.